HYBRID PEDAGOGICAL MODEL BERBASIS PERMAINAN TRADISIONAL PADA PENDIDIKAN JASMANI SECARA INKLUSIF: TINJAUAN LITERATUR SISTEMATIS - Ashar; Muhammad Wajdi; Sudarsono; Syarifah Nur Fajrin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to systematically review the literature related to the implementation of a hybrid pedagogical model that integrates traditional games with digital media in inclusive education. Using a Systematic Literature Review (SLR) approach to publications from the 2020–2026 period, this study highlights how the combination of local cultural values ​​and technological innovation can create a more adaptive, inclusive, and globally relevant learning experience. Thematic analysis identified five main focuses: (1) the integration of traditional games and digital media, which has been proven to improve motor, cognitive, and social skills while motivating participation; (2) teacher readiness and pedagogical models, including Teaching Games for Understanding (TGfU), which still face obstacles of anxiety and limitations of inclusive methodologies; (3) the digital divide and accessibility, which are major barriers to the application of technology in diverse educational contexts; (4) the use of AI-based technology for adaptive learning, which offers personalization and real-time feedback but raises ethical and privacy issues; and (5) research gaps in the form of a lack of longitudinal studies, the need for scalable solutions, and the lack of media literacy integration in physical education curricula. The study's findings confirm that the successful implementation of hybrid pedagogical models relies on ongoing teacher training, culturally responsive design, and digital policy and infrastructure support. This research provides important contributions to development practice, policy, and future research, emphasizing the need for strategies to bridge the digital divide and strengthen inclusive educational innovation.